PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE FORMULATE-SHARE-LISTEN-CREATE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS IX SMPN 2 LUBUK ALUNG - Firzatinnajmi, Ulfia (Departemen Matematika, 2023)
Mathematical communication is one of the aspects that has a significant importance that must be accomplished in the learning process, especially in mathematics. Based on the observation in SMPN 2 Lubuk Alung, it shows that the matematical comunication ability of students in class IX is still not optimal. An alternative way to solve this problem is by using the Formulate-Share-Listen-Create (FSLC) model. The purpose of this study is to determine the effect of mathematical comunication skills on student who learn using the FSLC model better than students who learn using a direct learning model. This kind of research is a quasi-experiment through a Non-Equivalent post-test only control group design. The target population in this study is students in grade IX of SMPN 2 Lubuk Alung in 2023/2024 academic year. The sampling process was implemented through a simple random samping technique. The instrument used is presented in the form of a final test of mathematical communication ability. Based on the results of the final hypothesis testing, the P-value = 0,004 is achieved with a real standard of 0,005, which means that the P-value < and therefore the is rejected. Hence, it can be conclude that there is an effect on the mathematical communication ability of students after studying by applying the FSLC model.Keywords – Formulate-Share-Listen-Create (FSLC), Mathematical Communication Skills.